If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4B + -32B = 36B + -8BY Combine like terms: 4B + -32B = -28B -28B = 36B + -8BY Solving -28B = 36B + -8BY Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Add '-36B' to each side of the equation. -28B + -36B = 36B + -36B + -8BY Combine like terms: -28B + -36B = -64B -64B = 36B + -36B + -8BY Combine like terms: 36B + -36B = 0 -64B = 0 + -8BY -64B = -8BY Add '8BY' to each side of the equation. -64B + 8BY = -8BY + 8BY Combine like terms: -8BY + 8BY = 0 -64B + 8BY = 0 Factor out the Greatest Common Factor (GCF), '8B'. 8B(-8 + Y) = 0 Ignore the factor 8.Subproblem 1
Set the factor 'B' equal to zero and attempt to solve: Simplifying B = 0 Solving B = 0 Move all terms containing B to the left, all other terms to the right. Simplifying B = 0Subproblem 2
Set the factor '(-8 + Y)' equal to zero and attempt to solve: Simplifying -8 + Y = 0 Solving -8 + Y = 0 Move all terms containing B to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + Y = 0 + 8 Combine like terms: -8 + 8 = 0 0 + Y = 0 + 8 Y = 0 + 8 Combine like terms: 0 + 8 = 8 Y = 8 Add '-1Y' to each side of the equation. Y + -1Y = 8 + -1Y Combine like terms: Y + -1Y = 0 0 = 8 + -1Y Simplifying 0 = 8 + -1Y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
B = {0}
| 6x-2-x=13 | | 11x+19=5x+1 | | 116-4x=32x+24 | | 24x^2+17x+3=0 | | 2(3y-5x)= | | x^20= | | 4x-5=2x+8 | | -2+18d=19d+10 | | -6a(a+3)= | | 5n-2=-2n+1 | | 4r-8r+8+r= | | 36-6y=18x-6 | | x^2+10+23=0 | | -18+54X=27 | | 14x^2+17x-6= | | Y=[[x+5]] | | 8(b-3)= | | 5x+2xw=7-4xy | | -3(2x-4)=8x | | -6(3+x)=-24 | | 15-5t=55 | | 60R-90R=70 | | 166-6x=6x | | 5-(3+t)=-1+2(-3+t) | | 4x^2-2x-16=0 | | x(6-1)-2=13 | | 4x+8x-4=3(4x+3) | | -6.30=4.2m | | ln(2x)*2= | | 2x^2-5x-16=0 | | 45t=40(+1) | | 240x-140=20(12x-7) |